Fluorıde Applıcatıons - Firdevs Tulga (Galenos Yayinevi, 1998)
The decline in the caries incidence observed in the developed countries is attributed to the widespread fluoride applications. In this article, systemic and topical fluoride applications are reviwed with emphasis on the necessity of fluoride applications in every level of our community and especially in caries-prone children.